2019
DOI: 10.1002/jlb.6ri0319-094r
|View full text |Cite
|
Sign up to set email alerts
|

When the balance is broken: X-linked gene dosage from two X chromosomes and female-biased autoimmunity

Abstract: Women and men exhibit differences in innate and adaptive immunity, and women are more susceptible to numerous autoimmune disorders. Two or more X chromosomes increases the risk for some autoimmune diseases, and increased expression of some X-linked immune genes is frequently observed in female lymphocytes from autoimmune patients. Evidence from mouse models of autoimmunity also supports the idea that increased expression of X-linked genes is a feature of female-biased autoimmunity. Recent studies have begun to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 161 publications
0
35
0
5
Order By: Relevance
“…It seems that expression of the Toll-like receptors on the inactive X is partly responsible for the impressive sex differences in some cases of autoimmune diseases like Lupus and Sjogren disease. 36 Toll-like receptors, encoded by the X chromosome, are signaling pattern recognition receptors that are an integral part of innate immunity. The little extra activity may provide females with better protection against infectious agents, but it may make them more susceptible to autoimmunity.…”
Section: Escape Genes Influence Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…It seems that expression of the Toll-like receptors on the inactive X is partly responsible for the impressive sex differences in some cases of autoimmune diseases like Lupus and Sjogren disease. 36 Toll-like receptors, encoded by the X chromosome, are signaling pattern recognition receptors that are an integral part of innate immunity. The little extra activity may provide females with better protection against infectious agents, but it may make them more susceptible to autoimmunity.…”
Section: Escape Genes Influence Phenotypementioning
confidence: 99%
“…Studies in mice show that increasing the expression of the X-linked Toll-like receptors in susceptible mice increases the expression of the autoimmune disorder. 36 It has not yet been shown that affected females and Klinefelter males have greater expression of their Toll-like receptors than those women and XXY males who do not have the disorder.…”
Section: Escape Genes Influence Phenotypementioning
confidence: 99%
“…Firre RNA primarily regulates autosomal genes in the hematopoietic system, including in common lymphoid progenitors (Andergassen et al, 2019;Lewandowski et al, 2019). This observation may prove relevant to sex differences in autoimmune disorders (Syrett and Anguera, 2019), as the FIRRE locus was also recently identified as differentially methylated in CD4 + memory T cells of twins discordant for multiple sclerosis (Souren et al, 2019). While global trans-acting FIRRE/Firre RNA functions are well beyond the scope of this perspective, it appears that many autosomal targets function in RNA splicing, processing and transport, likely due to FIRRE/Firre RNAs physical association with HNRNPU (Hacisuleyman et al, 2014;Bergmann et al, 2015).…”
Section: Dissecting Tandem Repeat Dna and Rna Functions In Vivomentioning
confidence: 94%
“…In terms of disease susceptibility there is ample evidence suggesting that sex bias in X-linked gene expression play a role. For example, having two X chromosomes increases the risk of developing autoimmunity [reviewed in Syrett and Anguera (2019)]. This phenomenon may be a result of unusual XCI patterns in immune cells, which could leave certain X-linked genes involved in immune response susceptible to reactivation (Wang et al, 2016; Syrett et al, 2019).…”
Section: Role Of X-linked Genes In Sex Differences and In Diseasementioning
confidence: 99%